Manejo de labores culturales del cultivo de cacao (Theobroma cacao L.) de la finca Dos hermanos en la ciudad de Montalvo - Junco García, Dennys (2019)
This study was intended to be able to cooperate from the technical-agricultural point of view with the community of "La Maritza" located in the city of Montalvo, in order to provide possible solutions regarding the management of cultural work applied in cultivation of cocoa (Theobroma cacao L.), during the study it was selected the realization of the production factors were not carried out in a technical way which is with a decrease at the time of harvest, reflecting economic losses, which was recommended to perform field days, links with the community and undergraduate thesis to improve as much as possible the problem raiseD